Just a minute : why humans tell time - Hudson, Kirstie, 1976-; Polak, Monique (Orca timeline, 2025)
"Part of the nonfiction Orca Timeline series for middle-grade readers, this illustrated book is a comprehensive overview of time, and how and why we measure it."--